Electrical and photoelectrical properties of iodine modified porous silicon on silicon substrates - Olenych, І.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Current-voltage characteristics, spectral dependences of photovoltage and short-circuit current of the structures based on porous silicon at adsorption of iodine molecules are presented. It is revealed widening the spectral range of photosensitivity in the samples in short-wavelength range as compared with that of single crystal silicon. Kinetics of the photovoltage response inherent to the porous silicon-silicon structures has been investigated. The results are explained in the frame of qualitative model that involves formation of p-n-transitions in these structures as a result of inversion of the conductivity type in porous silicon nanocrystals under the influence of adsorption of molecular iodine